Energy-Proportional Computing: A New Definition - Sen, Rathijit; Wood, David A. (IEEE Computer, 2017)
A new energy-proportional computing model extends Barroso and Holzle's original definition for fixed-resource systems to aid in the design of more efficient modern systems with reconfigurable resources that can be varied at runtime.